FORM OF PRESENTATION OF UMAPOS DANCE IN BALANTAK TRIBAL COMMUNITY - Jamilah Jamilah; Heriyati Yatim; Andi Padalia (JURNAL PAKARENA, 2022)
This study aims to find out and describe the Form of Presentation of Umapos Dance in the Balantak Tribe Community in Luwuk Banggai Regency, Central Sulawesi. This research uses a descriptive qualitative approach, focusing on the Form of Umapos Dance Presentation in the Balantak Tribe Community in Luwuk Banggai Regency, Central Sulawesi. Data are obtained through observation or observation, interviews, and documentation. Data analysis is carried out by reducing the data and inferring the data correctly. The results showed that the form of presentation of Umapos Dance in the Balantak Tribal Community in Luwuk Banggai Regency, Central Sulawesi, namely: Performers or dancers, Movements, dance accompaniment music, Floor patterns, makeup and clothing, property, and performance venues. This Umapos dance performance in ancient times was a series of Sumoili and Ummusulen dances for the repellent of danger to lower the seawater. Although these three dances are a series, they can still be performed separately or stand-alone. The later development of this dance was not only performed for rituals as well as for welcoming guests.